Cabochiens at the Hotel Saint-Pol (engraving) - G. Burgun (Wikimedia Commons, 1860)
Notice iconographique issue de Wikimedia Commons. Titre: Cabochiens at the Hotel Saint-Pol (engraving). Cabochiens at the Hotel Saint-Pol (engraving)
Droits : Licence Public domain via Wikimedia Commons
Keywords: iconographie; illustration; gravure; patrimoine; wikimedia commons; Iconographie